Complexity and Health Coaching: Synergies in Nursing. (11th September 2013) - Mitchell, Gail J.; Cross, Nadine; Wilson, Michelle; Biernacki, Shauna; Wong, Winnie; Adib, Behnam; Rush, Danica
Abstract : Health care professionals are increasingly aware that persons are complex and live in relation with other complex human communities and broader systems. Complex beings and systems are living and evolving in nonlinear ways through a process of mutual influence. Traditional standardized approaches in chronic disease management do not address these non-linear linkages and the meaning and changes that impact day-to-day life and caring for self and family. The RN health coach role described in this paper addresses the complexities and ambiguities for persons living with chronic illness in order to provide person-centered care and support that are unique and responsive to the context of persons' lives. Informed by complexity thinking and relational inquiry, the RN health coach is an emergent innovation of creative action with community and groups that support persons as they shape their health and patterns of living.